In-channel amperometric detection for microchip electrophoresis using a wireless isolated potentiostat - Gunasekara, Dulan B. (2011)
The combination of microchip electrophoresis (ME) with amperometric detection leads to a number of analytical challenges that are associated with isolating the detector from the high voltages used for the separation. While methods such as end-channel alignment and the use of decouplers have been employed, they have limitations. A less common method has been to utilize an electrically isolated potentiostat. This approach allows placement of the working electrode directly in the separation channel without using a decoupler. This paper explores the use of microchip electrophoresis and electrochemical detection (ME-EC) with an electrically isolated potentiostat for the separation and in-channel detection of several biologically important anions. The separation employed negative polarity voltages and tetradecyltrimethylammonium bromide (TTAB, as a buffer modifier) for the separation of nitrite (NO(2)(-)), glutathione (GSH), ascorbic acid (AA), and tyrosine (Tyr). A half-wave potential (E(½)) shift of approximately negative 500 mV was observed for NO(2)(-) and H(2)O(2) standards in the in-channel configuration compared to end channel. Higher separation efficiencies were observed for both NO(2)(-) and H(2)O(2) with the in-channel detection configuration. The limits of detection were approximately two-fold lower and the sensitivity was approximately two-fold higher for in-channel detection of nitrite when compared to end-channel. The application of this microfluidic device for the separation and detection of biomarkers related to oxidative stress is described.